TEACHING WRITING OF RECOUNT TEXT BY USING PERSONAL LETTER AS MEDIA IN THE TENTH GRADE AT MAN JUNG CANGCANG PAMEKASAN - Nur Farida (The Ellite of Unira, 2021)
This research aims are to describe the teacher in using personal letter as media in teaching writing of recount textand tofind out the teacher’s problems in teaching writing of recount text by using personal letter as media in the tenth grade of MAN Jung Cangcang Pamekasan. Then, the object of this research obtain from the students of the tenth grade atMAN Jung Cangcang Pamekasan. There are 35 that consist 9 boys and 26 girls students. In gathering the data, the reseacher used observation process, interview, and documentation at the tenth grade of MAN Jung Cangcang Pamekasan. The research design of this study is descriptive qualitative. The result of this research, there are how the teacher in using personal letter and the problems the teacher in using personal letter as media in the tenth grade at MAN Jung Cangcang Pamekasan. In using personal letter of teaching writing recount text, there are some steps such as: pre-activity, whilst activity, and post activity. Then, the problems that was faced by the teacher in usingpersonal letter as media in teaching writing recount text are the first,the teachers’ problems in teaching writing recount text is difficult to get attention for students in teaching process by using personal letter media, the second problem, the teacher felt difficult to make the students activein the class because the students less of vocabularies, and the third problem, the teacher felt that the goal of the teaching process by using personal letter as media is not running well.